SAT0678 DEVELOPMENT AND VALIDATION OF A SELF-ADMINISTRATED QUESTIONNAIRE MEASURING ESSENTIAL KNOWLEDGE FOR PATIENTS WITH SPONDYLOARTHRITIS : THE SPONDYLOARTHRITIS ASSESSMENT KNOWLEDGE QUESTIONNAIRE(SPAKE):. (June 2019) - Beauvais, Catherine; Pereira, Bruno; Pham, Thao; Sordet, Christelle; Claudepierre, Pascal; Fayet, Francoise; Wendling, Daniel; Costantino, Felicie; Carton, Laurence; Grange, Laurent; Soubrier, Martin; Legoupil, Nathalie; et al.
Abstract : Background: Patient education is recommended for patients with inflammatory arthritis to enhance self-management. Only one Knowledge Questionnaire (KQ) is available in spondyloarthritis (SpA) (ref 1) and needs to be updated according to the recent recommendations for SA and the patients' needs (ref 2). Objectives: To develop and validate a new KQ in SpA Methods: 4 steps. Step1. Selection of knowledge considered essential for patients with SpA through Delphi rounds by a working group of rheumatologists, health professionals (HPs) and patients, leading to a list of consensual items (ref2). Step2. Two rheumatologists and a rheumatology nurse constructed the first version of the KQ, each question of the KQ referring to a selected item on the list. The formulation was then amended by the working group. A new version was elaborated during a face-to-face meeting of 3 health professionals and one patient. Step3. The KQ was submitted to ten patients for cognitive debriefing, comments were analyzed and a final version was elaborated. Step 4. Multicentric validation in 13 rheumatology departments: acceptability was measured by the rates of missing data per item, reproducibility and sensitivity to change were assessed respectively by test/retest at a 2 weeks interval (Lin's concordance correlation coefficient) and by testing the KQ before and after patient education sessions. Results: Step1 obtained 42 items, 32 considered essential and 10 considered useful, selected respectively by more than 2/3 or more than 50% of participants to the Delphi rounds, leading to the SPAKE: a 42-items questionnaire, with a 32-items short form. The SPAKE contains 6 knowledge domains: disease knowledge (12 items), pharmacological treatment (11), non -pharmacological treatment (8), comorbidities (1), self-care for pain and fatigue (4), adaptative skills to psychosocial, professional issues and health care system (6). The validation included 130 patients, 67 (51.5%) men, mean age 43.5±12.9 years, median disease duration 8 years [3;16]. There were no missing items in the KQ. The SPAKE's internal validity (Kuder-Richardson) was 0.85. Reproducibility (in 61 patients) was 0.81 [95% CI, 0.72; 0.89]. Sensitivity to change was measured in 55 patients. A statistically significant difference in total knowledge score was observed between the two assessment times: 29.1±6.4 vs. 34.7±5.9 (p<0.001), representing an effect size of 0.92 [0.52; 1.31]. The questionnaire's external validity was confirmed by a significant correlation with the patients' educational level (p=0.02). Conclusion: This study enabled the development and the validation of the SPAKE, a knowledge questionnaire for patients with SpA, with a good acceptability, reproducibility and sensitivity to change. This KQ will be helpful to assess the process of knowledge acquisition in patient education approaches. References: [1] Lubrano E, et al. Br J Rheumatol. 1998;37:437-41.2 Beauvais C, et al. ARD 2015; 74, suppl 2 Disclosure of Interests: Catherine Beauvais: None declared, Bruno Pereira: None declared, Thao Pham Speakers bureau: Lilly, Novartis, Christelle Sordet: None declared, Pascal Claudepierre Consultant for: Honoraria from Novartis as steering committe of this survey, Francoise Fayet: None declared, Daniel Wendling: None declared, Felicie Costantino: None declared, Laurence Carton Grant/research support from: AMGEN UCB MYLAN BIOGARAN BIOGEN PFIZER LILLY GRUNENTHAL TEVA NOVARTIS JANSSEN EXPANSCIENCE SANOFI THUASNE MSD GENEVRIER ABBVIE, LAURENT GRANGE Consultant for: Laurent Grange has received honoraria from Amgen, Lilly and UCB and research support from Lilly, Amgen, UCB, Expanscience, Mylan, Roche diagnostics and TEVA, Martin SOUBRIER: None declared, Nathalie Legoupil: None declared, Aleth Perdriger: None declared, Isabel Tavares: None declared, Emmanuelle Dernis: None declared, Laure Gossec Grant/research support from: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis-Sandoz, Pfizer, Sanofi, and UCB, Consultant for: AbbVie, Biogen, BMS, Celgene, Janssen, Lilly, MSD, Nordic Pharma, Novartis-Sandoz, Pfizer, Roche, Sanofi, and UCB, Consultant for: L Gossec has received honoraria from Celgene as investigator for this study, Malory RODERE: None declared